(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The research tried to show the importance of Administrative Control being one of the important means in administrative work; they work on the review and audit work done and error handling explored in the work and prevent the occurrence and ascertain the extent of implementation of the planned targets, and therefore this is reflected in raising the efficiency of the performance of the tax examiner and complete the work as soon as possible and the highest efficiency and reduce the gaps that may occur between the parties of the tax settling accounts and dealt with in the theoretical side of the search to the research problem, namely with whether operating management oversight to improve the performance and increase the efficiency of the work of the tax examination and it is an application leads to the discovery of errors during the examination process, the research aims to shed It highlights the importance of the adoption of the administrative control of the tax examination procedure measures as they represent an episode of the administrative process, which seeks to make sure that work is going on according to the goals set loops, and was based on research at the head of the hypothesis that ((there is a correlation statistically significant differences between the administrative control and improved efficiency tax view )).